The Effect of Solvent Type on Oil Yield on Essential Oil of Sweet Orange Peel Extract (Citrus X Sinensis) - Anwar Syahadat; Hasni Yaturramadhan; Ayus Diningsih (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2021)
Introduction: Citrus fruits can be processed into various types of preparations that are very useful. Sweet orange (Citrus X sinensis) is a type of orange that is consumed by squeezing it into a drink. So far, sweet orange peels (Citrus X sinensis) have not been fully utilized and become waste that is thrown away. Meanwhile, the peels of citrus fruits have useful content, so that the peels of citrus fruits can be processed into products that are useful for the community. Wet sweet orange peel is better to use than dried sweet orange peel. This is because the sweet orange peel contains essential oils which have not completely evaporated so that the oil can be taken directly. Method: This research is a laboratory-based experimental study. Results: From the analysis, it was found that the water content of sweet orange peel was 75.5%. The results of data analysis showed that the highest oil yield was obtained using the soxhletation method for 12 hours using 6.15% hexane as a solvent, 4.89% ethanol as a solvent, and 1.67% aquadest as a solvent. When compared to these three solvents, hexane solvent is more effective than ethanol and aquadest. It shows that in general the essential oil from lime peel produced is still within the range of essential oil quality standards based on ISO 3519:2005. Conclusion: In this study, the best solvent was hexane. The sweet orange peel essential oil produced has a greenish yellow color for hexane and aquadest solvents and yellowish green for ethanol solvents. The essential oil produced has a density of 0.8580 g/cm3.